GREEN LEARNING SPACE AS AN AUTHENTIC LEARNING ENVIRONMENT TO IMPROVE ELEMENTARY STUDENTS' SCIENCE ACHIEVEMENT - Jaka Waluya; Epon Ningrum; Iwan Setiawan; Amin (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
IPAS instruction in elementary schools is still dominated by the lecture method, resulting in students having limited opportunities for hands-on learning experiences. This study aims to analyze the effect of implementing a Green Learning Space through the use of an open green garden on students’ learning outcomes and learning activities in the IPAS subject. The study employed a quantitative approach using a pre-experimental method with a One-Group Pretest–Posttest Design. The study was conducted with 24 third-grade students at SDIT Nurul Iman Pondok Bambu, East Jakarta, who were selected using total sampling. Data were collected through achievement tests, observations of learning activities, and student response questionnaires. The data were analyzed descriptively using mean scores, the percentage of learning mastery, the percentage of learning activities, and Normalized Gain (N-Gain). The results showed that the average learning achievement increased from 64.13 on the pretest to 81.33 on the posttest, with the percentage of learning mastery rising from 8.33% to 87.50%. The N-Gain value of 0.48 falls into the moderate category. Additionally, student learning activity reached an average of 82.64%, indicating an active category during the learning process. Thus, the implementation of the Green Learning Space effectively improves student learning outcomes and learning activity while providing a more contextual, meaningful, and student-centered learning experience.